Healthcare Access and Experiences of Ahıska Migrant Women in Turkey: A Qualitative Phenomenological Study - Toker, Oguzhan; Dikmen, Mualla (Springer, 2026)
Although Turkey has become a central focus in migration research, the healthcare experiences of smaller, historically displaced groups-and the barriers they encounter-remain largely overlooked. One such group is the Ah & imath;ska Turks, whose forced migration history spans from the Caucasus to Central Asia and, more recently, to Turkey. Despite cultural and linguistic proximity to the host population, Ah & imath;ska Turk migrant women face persistent challenges in accessing healthcare due to linguistic, systemic, and gender-based barriers. The objective of this study was to explore Ah & imath;ska Turk migrant women's experiences of accessing healthcare services in Turkey, with a particular focus on the barriers they encounter and the strategies they use to navigate the healthcare system. This qualitative phenomenological study was conducted with 20 Ah & imath;ska Turk migrant women residing in temporary accommodation centers in Elaz & imath;& gbreve;, Turkey. Participants were selected using purposive sampling. Data were collected through semi-structured, in-depth interviews conducted between February and April 2025 and were analyzed thematically following Braun and Clarke's framework. Three key themes emerged: (1) Reasons for Healthcare Utilization - participants prioritized children's health over their own, delaying personal care; (2) Facilitators and persistent barriers - language difficulties, unfamiliarity with the health system, and ethnic misidentification were common obstacles; (3) Recommendations - participants suggested interpreter services, access to female providers, and clearer guidance through the system. Ah & imath;ska Turk women's experiences indicate that formal access to healthcare services does not necessarily translate into equitable care. While many participants demonstrated resilience, they continued to encounter structural and interpersonal barriers that shaped their healthcare experiences. By focusing on women's healthcare access experiences, perceived barriers, and everyday strategies for navigating health services, this study brings attention to the specific ways in which an under-researched migrant group engages with the healthcare system. The findings highlight the importance of culturally sensitive, linguistically inclusive, and gender-responsive healthcare practices to promote equity within increasingly diverse healthcare systems.
Keywords: Migrant Women; Ah & Imath;Ska Turks; Healthcare Access; Health Equity